Development of Progressive Islamic Law in Indonesia Regarding ‘Apostasy’ as Grounds for Divorce: Insights from Maqasid Sharia - Huda, Miftakhul; Shofia, Niska; Solehudin, Ending; Rozikin, Opik; Ahyani, Hisam (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2022)
The development of Islamic law in Indonesia, particularly concerning apostasy as a cause of divorce, is significant in the evolution of Islamic law. The complexity of Indonesia's social and legal system poses challenges in integrating Islamic values with societal diversity. This research aims to understand the development of Islamic law in Indonesia regarding apostasy issues through the analysis of maqasid sharia. Using a descriptive-analytical approach, data from various sources are examined to understand the development of Islamic law in Indonesia, focusing on the implications of maqasid sharia regarding apostasy as a reason for divorce. Findings indicate that progressive Islamic law development in Indonesia emphasizes a balance between religion and individual justice, protecting individual rights in divorce and seeking fair solutions through legal reforms considering the principles of maqasid sharia.